LeChatelier-Samuelson principle in games and pass-through of shocks - Alexei Alexandrov; Özlem Bedre-Defolie (European School of Management and Technology (ESMT), 2015)
The LeChatelier-Samuelson principle ("the principle") states that as a reaction to a shock, an agent's short-run adjustment of an action is smaller than the long-run adjustment of that action when the other related actions can also be adjusted. We extend the principle to strategic environments and to shocks that affect more than one action directly. We define long run as an adjustment that also includes the affected player adjusting its other actions and other players adjusting their strategies. We show that the principle holds for 1) supermodular games (strategic complements), 2) submodular games (strategic substitutes) for shocks that affect only one player's action directly and when the players' payoffs depend only on their own strategies and the sum of the rivals' strategies (for example, homogeneous Cournot oligopoly). We also provide other sufficient conditions for the principle to hold in games of strategic substitutes. Our results imply that when the principle holds a multiproduct oligopoly might have lower cost pass-through in the short run than in the long run. Hence, we argue that the principle might explain the empirical findings of overshifting of cost and unit tax by multiproduct firms.
urn:nbn:de:101:1-201511234290; More recent version: http://hdl.handle.net/10419/149864
Keywords: 650